2018
DOI: 10.5468/ogs.2018.61.5.553
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation and management of endometriosis: guideline for Korean patients from Korean Society of Endometriosis

Abstract: Endometriosis is one of the most common diseases in reproductive ages, and it affects patients' quality of life and fertility. However, few Korean guidelines are available for the evaluation and management of endometriosis. Korean Society of Endometriosis reviewed various literatures and trials, and to provide seventy-one evidence-based recommendations. This review presents guidelines for the diagnosis and management of endometriosis with emphasis on: it's role in infertility, treatment of recurrence, asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 66 publications
1
32
0
10
Order By: Relevance
“…Despite the differences, both of these guidelines recommend that medical treatment including hormonal contraceptives, progestogens and GnRH analogues, do not constitute effective approaches towards improving fertility rates in patients presenting with endometriosis and thus should not be offered on this indication alone [ 87 , 98 ]. Guidelines provided from other organizations, including the Korean Society of Endometriosis are generally in the same line with the directions provided by ESHRE [ 99 ]. The guidelines provided by the Clinical Practice Gynaecology Committee and the Executive and Council of the Society of Obstetricians and Gynaecologists of Canada albeit they provide robust data, nonetheless, the do not provide specific guidance regarding to the optimal treatment protocol for managing endometriosis-related infertility [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the differences, both of these guidelines recommend that medical treatment including hormonal contraceptives, progestogens and GnRH analogues, do not constitute effective approaches towards improving fertility rates in patients presenting with endometriosis and thus should not be offered on this indication alone [ 87 , 98 ]. Guidelines provided from other organizations, including the Korean Society of Endometriosis are generally in the same line with the directions provided by ESHRE [ 99 ]. The guidelines provided by the Clinical Practice Gynaecology Committee and the Executive and Council of the Society of Obstetricians and Gynaecologists of Canada albeit they provide robust data, nonetheless, the do not provide specific guidance regarding to the optimal treatment protocol for managing endometriosis-related infertility [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lesson from this case is that we should try not to pass through the bladder when taking ova, especially for those patients with chocolate cysts, not only because of some recent complications like bladder bleeding, but also for possible long-term complications, for example, the cyst fluid may aggravate pelvic adhesion and active endometrium may plant in pelvic organs such as the uterus or even the bladder forming new endometriosis leisions. The current guideline also recommends ovarian cystectomy, instead of drainage or coagulation [7]. However sometimes the pelvic adhesion in patients with endometriosis is so serious that it is difficult to avoid passing through the bladder and puncturing the cyst fluid when retrieving the eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The guideline for treatment and approaching adolescents with endometriosis is based on studies examining adult women due to the limited number of studies focusing specifically on adolescents. It is recommended that the decision for surgical management of endometriosis should be based on clinical evaluation, imaging modality, and medical treatment response, with restrictive use of laparoscopy for diagnosis (Hwang et al, 2018). Although many clinicians prescribe gonadotropin-releasing hormone agonists to reduce inflammation, blood flow, and adhesions in endometriosis, research has shown that preoperative hormonal treatment may not reduce either endometriosis related pain or recurrence (Dunselman et al, 2014;Rolla, 2019).…”
Section: The Physical Painmentioning
confidence: 99%